Case Report: A rare case of hemoptysis: multiple vascular variations - Zhang, Beining; Wang, Jiangye; Zheng, Ninggang (Frontiers in Medicine, 2025)
Bronchial artery embolization (BAE) is an effective treatment for hemoptysis, with potential complications including pain and spinal ischemia. We report a rare case in which the right bronchial artery communicated with the right intercostal arteries, and the right intercostal artery had an anastomosis with the right vertebral artery. Additionally, the left bronchial artery was found to have a connection with the left vertebral artery.